Genetic studies on yield and oil quality in sunflower (Helianthus annuus L.): Genetic studies on yield and oil quality in sunflower (Helianthus annuus L.) - S VISWABHARATHY; P L VISWANATHAN; S MANONMANI; R CHANDIRAKALA (Journal of Oilseeds Research, 2020)
Sunflower oil with high oleic acid content has nutritional benefit similar to olive oil. Forty five sunflower genotypes with varying oleic acid content were evaluated for the estimation of proportion of heritability, genetic advance, PCV and GCV for ten quantitative traits during kharif 2018. PCV was higher compared to GCV for all the traits. High PCV and High GCV were observed for seed yield per plant, hundred seed weight, oil yield and linoleic acid content. Seven characters viz., plant height, head diameter, hundred seed weight, seed yield/plant, oil yield, oleic acid content and linoleic acid content recorded high heritability followed by high genetic advance indicating the presence of additive gene action and are efficient for selection.